Regime jurídico das negociações bursáteis - Jose Elias Alvarenga de Padua (2014)
Trading in stock exchange is the key to the Stock Market which can bring a social and economical development to a country. Despite the complexity and uncertainty, investors see stock exchanges trading as a simple and safe deal and they are not interested in knowing the tradings procedures. While technology tools and mutual trust among its participants are responsible for reducing the complexity of trading in stock exchange, contractual system and its legal relationships are hidden and unknown. This hampers the correct understanding of their legal status and allows non-technical uses and misinterpretations of its legal precepts. In this context we intend to examine the trading in stock exchange under a strictly legal point of view. We want to identify and analyze several legal relationships formed in contractual system where the trading in stock exchange happens and understand its operation and safeguard mechanisms.